2013
DOI: 10.1016/j.cell.2013.08.030
|View full text |Cite
|
Sign up to set email alerts
|

A Nondegenerate Code of Deleterious Variants in Mendelian Loci Contributes to Complex Disease Risk

Abstract: Summary Whereas countless highly penetrant variants have been associated with Mendelian disorders, the genetic etiologies underlying complex diseases remain largely unresolved. Here, we examine the extent to which Mendelian variation contributes to complex disease risk by mining the medical records of over 110 million patients. We detect thousands of associations between Mendelian and complex diseases, revealing a non-degenerate, phenotypic code that links each complex disorder to a unique collection of Mendel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(236 citation statements)
references
References 59 publications
4
229
2
1
Order By: Relevance
“…As an example, a surprising correlation between complex diseases and Mendelian loci was revealed in a recent study, where records from 100+ million patients in Denmark and the United States were analyzed [8]. In a different scenario, Li Li et al (2014) combined data from genome association studies together with EHR records to find novel trait-disease associations, such as an increase in mean corpuscular volume before the onset of acute lymphoblastic leukemia [9].…”
Section: This Article Is Part Of the Topical Collection On Patient Famentioning
confidence: 97%
“…As an example, a surprising correlation between complex diseases and Mendelian loci was revealed in a recent study, where records from 100+ million patients in Denmark and the United States were analyzed [8]. In a different scenario, Li Li et al (2014) combined data from genome association studies together with EHR records to find novel trait-disease associations, such as an increase in mean corpuscular volume before the onset of acute lymphoblastic leukemia [9].…”
Section: This Article Is Part Of the Topical Collection On Patient Famentioning
confidence: 97%
“…Role of genetic factors in the etiology of complex diseases remains largely unresolved. Using genome-wide associations in millions of patient medical records, a study demonstrated that common variants associated with complex diseases are enriched in the genes indicated by the "Mendelian code" -a phenotypic code that links each complex disorder to a unique collection of Mendelian loci (Blair et al 2013 ). The study identifi ed widespread comorbidity between Mendelian-Mendelian and Mendelian-complex disease pairs.…”
Section: Applications Of Neurogenomics In Neurological Disordersmentioning
confidence: 99%
“…Co-morbidity has several consequences including complicating the dissection of the biological mechanisms responsible for the distinct disorders; however, these co-morbidities may also provide a way for accessing information on these complex disorders. This has been elegantly shown recently, by Blair and colleagues, who demonstrated an association between Mendelian disorders and other complex conditions, subsequently showing that the Mendelian variants are probably contributing to disease risk for a range of complex diseases, providing a 'unique insight into the aetiology of complex diseases' (Blair et al, 2013). Furthermore, a recent genome-wide analysis aimed at finding a signal in the noise, led to the identification of risk loci with shared effects on five major psychiatric disorders (Cross-Disorder Group of the Psychiatric Genomics Consortium, Genetic Risk Outcome of Psychosis (GROUP) Consortium, 2013).…”
Section: Introductionmentioning
confidence: 95%